No change in key HIV target cell markers following initiation of three progestin-based hormonal contraception methods: findings from the CHIME study - Young, Marisa R.; Mehta, C. Christina; Staple, Tyree; Herring, Gina Bailey; Govindaraj, Sakthivel; Ibegbu, Chris; Herold, Betsy C.; Velu, Vijayakumar; Haddad, Lisa B.; Smith, Alicia K. (Frontiers in Immunology, 2025)
IntroductionDepot medroxyprogesterone acetate (DMPA) injectable, etonogestrel subdermal implant (ENG-implant), and levonorgestrel intrauterine device (LNG-IUD) are effective, widely used female hormonal contraceptives (HC). Observational studies, but not a randomized trial, suggest increased risk of HIV acquisition with HC use, particularly DMPA. Sexual acquisition of HIV occurs via CD4+ T cells expressing C-C chemokine receptor type 5 (CCR5), though other immunologic cells play a role. This study examined longitudinal changes in CCR5+ T cells and other immunologic cells in the female genital tract following HC initiation.MethodsHIV negative participants aged 18–45 years, not using HC, were recruited in Atlanta, Georgia. After two pre-HC visits, participants initiated DMPA, ENG-implant, or LNG-IUD and completed visits every three months for one year. Specimens (peripheral blood, endocervical cells, cervical tissue biopsy, and cervicovaginal lavage [CVL]) were analyzed for immune cellular markers (CD45, CD3, CD4, CCR5, CD69, HLA-DR, CD38, α4β7, CD103, Fox-P3, and Ki-67) using flow cytometry. Effects of CVL on HIV infection of cells in vitro was assessed. Vaginal microbiome was characterized via 16S rRNA gene amplicon sequencing. Multivariable linear mixed effects models estimated association between HC and immune markers (Primary outcome: proportion of CD4+ T cells expressing CCR5; Secondary outcomes: other immune markers, in vitro HIV enhancement). A Bonferroni correction was applied.ResultsAmong 118 participants (mean age 25.9; 44.1% self-identified as Black race), 545 visits were completed from 2019-2023. No significant changes were observed in proportion of CCR5+ T cells in any tissue type post-HC. There were statistically significant but moderate absolute decreases in proportion of CD45+ and CD4+ T cells in CVL, and CD4+ T cells in blood, and increased proportion of CD69+ T cells in blood post-HC. Post-HC CVL vs. pre-HC enhanced HIV infection of cells in vitro for all three HC groups (p<0.01) and was modified by the vaginal microbiome. There was also evidence of interaction by time and microbiome parameters for several other immune cells.DiscussionOur findings suggest that commonly used HC methods do not result in immunologic changes that increase HIV acquisition risk. However, HIV infection enhancement with post-HC CVL in vitro warrants further study.